Pendokumentasian Budaya Lokal Berbasis Digital oleh Komunitas Budaya dan Mahasiswa untuk Mendukung Pariwisata di Kabupaten Wakatobi, Sulawesi Tenggara: The Local Culture Documentation Base on Digital by Local Communities, and Student for Tourism Support in Wakatobi, Southeast Sulawesi - Rabani, La Ode; Basundoro, Purnawan; Bani, Adhi Rahman (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This article discusses digital-based documentation of local culture by utilizing cultural potential to support the development and promotion of tourism in Wakatobi Regency. The Local Culture Documentation Training in Wakatobi is very meaningful not only for the Wakatobi community, but also in the national context considering that Wakatobi is one of the 10 tourist destinations set by President Joko Widodo. With this position, digital-based documentation involving local cultural institutions and communities has also supported Wakatobi's tourism activity, which is now affected by the COVID-19 pandemic. This activity helped to develop a cultural community with students and students in cultural documentation in Wakatobi through several multimedia and digital-based techniques. The diversity of traditional dances that have high value in Wakatobi such as Balumpa, Lariangi, Honari Mosega, Posepa, and kenta-kenta dances. If those cultures are not properly documented digitally, then the threats and vulnerabilities to those cultures are increasingly real in front of our eyes, especially cultural interventions through technology so rapidly. In addition, good documentation is needed for maintaining the continuity and maintenance of cultural values in the Wakatobi community. In the end, this documentation in the future will be a guide and education for the young generation of Wakatobi from the cultural side.